HAK TUKAR AGAMA DALAM PERLEMBAGAAN MALAYSIA: KONFLIK ANTARA KEBEBASAN BERAGAMA DAN HUKUM ISLAM - Mohamed Adil, Mohamed Azam (Jurnal Syariah, 2019)
The question of freedom of religion is both emphasised in the Qur' an and in the Federal Constitution of Malaysia. It is however, on one side the Islamic jurists agreed that freedom of religion is guaranteed, on the other hand, apostates seem to have committed an offence under the Islamic Criminal Law. The punishment seems to have a conflict particularly with reference to Article 11 (1) and 5 (1) of the Federal Constitution. This article attempts to discuss the question of apostasy from the Islamic and Malaysian Laws perspectives with special reference to the issue of fundamental right of freedom of religion. It also highlights the conflict of laws that surrounding the punishment of apostasy in various respective states' laws in Malaysia.